Psychiatry Helpline Service at a multidisciplinary hospital in Karachi, Pakistan: Preliminary findings and challenges - Nadeem, Tania; Noorullah, Aisha; Shafique, Alviya; Irfan, Sunita; Rehmat, Shehnila; Khan, Murad Moosa (Journal of the Pakistan Medical Association, 2025)
Objective: To describe the pattern of calls received at a psychiatry helpline service of a tertiary care centre. Method: The retrospective, descriptive chart review was conducted at the Aga Khan University Hospital, Karachi, and comprised data of all calls and messages received by the Psychiatry Helpline Service from October 2019 to September 2022. Before the commencement of the service in 2019, a minimum level of specific training was a mandatory requirement for the nursing staff who were to act as the front end of the service. The helpline number was provided to all the patients who were discharged or left against medical advice, those attending outpatient clinics or were being followed up through consultation-liaison psychiatric services. The helpline was active from 8 am to 4 pm on weekdays only. Any messages received outside the specific time period were addressed on the next working day. On receiving a call or message, basic socio-demographic details and queries were recorded online. Data collected by the nursing staff was later recorded in a database. Results: Of the 4,547 calls received, 315(7%) related to 2019, while 1,825(40.13%) were received in 2022. Overall, 2,316(50.9%) callers were females. Most people used the helpline for dose adjustment 1,390(30.56%), followed by psychoeducation 828(18.2%). Of the 38(0.83%) calls related to suicidal ideation, 31(81.6%)) were made by females compared to 7(18.4%) by males. Conclusion: The psychiatry helpline service experienced a significant increase in patient contacts, indicating its growing utilisation, and underscoring the potential for expanding its scope within the organisation to further cater to patient needs. Key Words: Psychiatry helpline, Mental health services, Helpline utilisation.